Inclusion of oil from transgenic Camelina sativa in feed effectively supplies EPA and DHA to Atlantic salmon (Salmo salar) grown to market size in seawater pens - Tocher, Douglas R; Sprague, Matthew; Han, Lihua; Sayanova, Olga; Norambuena, Fernando; Napier, Johnathan A; Betancor, Mónica B (Elsevier, 2024)
Atlantic salmon were fed either a diet reflecting current commercial feeds with added oil supplied by a blend of fish oil and rapeseed oil (COM), or a diet formulated with oil from transgenic Camelina sativa containing 20% EPA+DHA (TCO). Salmon were grown from smolt to market size (>3kg) in sea pens under semi-commercial conditions. There were no differences in growth, feed efficiency or survival between fish fed the TCO or COM diets at the end of the trial. Levels of EPA+DHA in flesh of salmon fed TCO were significantly higher than in fish fed COM. A 140g fillet from TCO-fed salmon delivered 2.3g of EPA+DHA, 67% of the weekly requirement level recommended by many health agencies, and 1.5-fold more than the 1.5g of EPA+DHA for COM-fed fish. Oil from transgenic Camelina supported growth and improved the nutritional quality of farmed salmon in terms of increased “omega-3” supply for human consumers.